ASSOCIATION AMONG MATHEMATICAL CRITICAL THINKING SKILL, COMMUNICATION, AND CURIOSITY ATTITUDE AS THE IMPACT OF PROBLEM-BASED LEARNING AND COGNITIVE CONFLICT STRATEGY (PBLCCS) IN NUMBER THEORY COURSE - Zetriuslita Zetriuslita; Wahyudin Wahyudin; Jarnawi Afgani Dahlan (IKIP Siliwangi and I-MES, 2018)
This research aims to find out the association amongMathematical Critical Thinking (MCT) ability, Mathematical Communication, and Mathematical Curiosity Attitude (MCA) as the impact of applying Problem-Based Learning Cognitive Conflict Strategy(PBLCCS) in Number Theory course. The research method is correlative study. The instruments include a test for mathematical critical thinking skill and communication, and questionnaire to obtain the scores of mathematical curiosity attitude. The findings show that: 1) there is no association between critical thinking skill and mathematical curiosity attitude as the impact of applying problem-based learning cognitive conflict strategy, 2) there is no association between mathematical communication and curiosity attitude as the impact of applying problem-based learning and cognitive conflict strategy, and 3) the impact of applying problem-based learning cognitive conflict strategy is more influential in developing critical thinkingskillthan communication skill and curiosity.